‘Great in theory’: Women’s care experiences in relation to Australia’s national maternity Strategy—Qualitative survey responses - Paula Medway; Alison M. Hutchinson; Linda Sweet (PLoS ONE, 2025)
Background The provision of woman-centred maternity care in Australia is guided by a national Strategy released in November 2019 titled Woman-centred care: Strategic directions for Australian maternity services (the Strategy). The Strategy upholds four values (safety, respect, choice, and access) that underpin twelve principles of woman-centred care. Aim To examine the maternity care experiences of women in Australia and explore how these align with the stated values and principles of the Strategy. Methods A national online survey was undertaken between February and June 2023. Women who received all their maternity care in Australia since 1 January 2020 were invited to participate. The survey consisted of predominantly closed questions; however, six open-text questions were included to give participants the opportunity to provide in-depth responses about the Strategy and its values. This paper presents a qualitative content analysis of the free-text responses. Findings A completed survey was submitted by 1750 eligible participants, of whom 1667 provided 3562 qualitative responses included in this analysis. These showed that while the definition of safety provided in the Strategy favours physically safe care, the survey participants preferred a definition that was more holistic, providing for emotional and psychological safety. Participants expressed the need for respectful relationships with their maternity care providers where they felt listened to and heard. They wanted to be made aware of their choices and to have their maternity care decisions supported without coercion. Participants also desired access to continuity of care, particularly with midwives, and greater access to mental health support across the maternity care episode. Conclusion The intent of the national Strategy has not yet been fully realised. A nationally coordinated response is required if the Strategy is to move from policy to practice, ensuring that women in Australia receive true woman-centred maternity care as intended.